Perceraian Akibat Peralihan Agama: Studi Kasus Tentang Putusan Hakim Pengadilan Agama Gorontalo - Hamid Pongoliu (LP2M Institut Agama Islam Negeri Sultan Amai Gorontalo, 2015)
Each couple would not want a divorce, but sometimes there just are not inevitable problems that lead to domestic harmony fall apart and eventually divorced, and one of them is due to the conversion. This study is field research by taking the case from 2009 to 2013 that it have been decided the Gorontalo Religious Court judges. The results showed the issue of conversion is a complicated issue and is very influential in household harmony husband and wife who causes discord and eventual divorce. Conversion are included in the category of unbelievers who sparked a major problem that can not be reconciled, and came to the trial panel of judges decided to divorce. In addition, the conversion brought due to the difficulties set religious status of children, maintenance, education, finance, and about inheritance, community property between husband and wife.